Researching the vulnerable a guide to sensitive research methods - Liamputtong, Pranee, 1955- (SAGE, 2007)
Exploring the considerations and sensitivities of being a researcher faced with a subject group at the margins of society this text explores the ethical, practical and methodological implications of working with such groups.